The Social Return on Investment (SROI) of four microfinance projects - Riccardo Grazioli; Giampietro Pizzo; Lucia Poletti; Giulio Tagliavini; Francesco Timpano (European Investment Fund (EIF), 2020)
The paper develops an SROI (Social Return on Investment) analysis of four microfinance institutions (MFIs) located in Spain, Italy and Bosnia-Herzegovina. This work is part of the MeMI Project ("Measuring Microfinance Impact in the EU. Policy recommendations for Financial and Social Inclusion") funded by the EIBURS. It is an attemptto translate microcredit outcome indicators into a social return, quantified in monetary terms. After preliminary focus group analyses and staff interviews, data on outcomes of selected microcredit lines have been collected through a questionnaire administered to the borrowers. By comparing the monetary value of these outcomes (translated into an estimated impact) with the amount of related investment, we find that SROI is greater than 2 for all the credit lines analysed, meaning that every euro invested in microcredit generates at least 2 euros of social return. We also find SROI ranging between 2.33 and 6.97, mirroring the differences between MFIs in terms of target, operating model and country-level financial environment. Although the analysis is conducted on a limited number of cases and SROI calculation can be sharpened, it shows how different factors and outcomes drive the social return generated by microcredit.
Keywords: 330; Mikrofinanzierung; Return on Investment; Soziale Integration; Projektbewertung; Spanien; Italien; Bosnien-Herzegowina